2013
DOI: 10.1186/1471-2334-13-551
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of diphtheria toxoid IgG antibodies in children, adolescents and adults in Poland

Abstract: BackgroundRecommendations for diphtheria immunization are to apply an effective primary immunization in infancy and to maintain immunity throughout life. Immunity against diphtheria depends primarily on antibody to the diphtheria toxin. This study evaluated the seroprevalence of IgG diphtheria antitoxin in sera of healthy children, adolescents and adults in Poland.MethodsA total of 1387 serum samples collected between 2010 and 2012 from individuals with ages ranging from 1 month to 85 years were investigated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 23 publications
1
23
0
1
Order By: Relevance
“…Certainly, more recent diphtheria vaccination is a strong predictor of immunity in adults 7 and children, 21 where booster vaccines coincide with increasing antibody titre. 22 The combination of immunization (complete or partial) and natural challenge through exposure may also contribute to a quantitatively different level of response in areas where the reservoir of bacteria is relatively larger. We were unable to include in our analysis the time since immunization with specific vaccines, the inclusion of which would have helped to explore this further.…”
Section: Discussionmentioning
confidence: 99%
“…Certainly, more recent diphtheria vaccination is a strong predictor of immunity in adults 7 and children, 21 where booster vaccines coincide with increasing antibody titre. 22 The combination of immunization (complete or partial) and natural challenge through exposure may also contribute to a quantitatively different level of response in areas where the reservoir of bacteria is relatively larger. We were unable to include in our analysis the time since immunization with specific vaccines, the inclusion of which would have helped to explore this further.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were obtained in other Polish studies, showing that up to 30% lacked the adequate protective level of diphtheria antibodies, even though a high percentage of children had undergone vaccinations in accordance with the official schedule. [11,12] …”
Section: Discussionmentioning
confidence: 99%
“…Optical density was measured at 450/620 nm and antitoxin levels were determined by standard curves. According to manufacturer-recommended thresholds and the work of previous studies (13,17,21), the results were classified into 3 groups. The diphtheria groups were as follows: susceptibility (antitoxin level <0.1 IU/ mL), full protection (antitoxin level >1 IU/mL), and basic protection (antitoxin level >0.1 IU/mL and <1 IU/mL).…”
Section: Methodsmentioning
confidence: 99%
“…Prior studies have reported on diphtheria and tetanus immunity status in different populations (9)(10)(11)(12)(13). Some have studied special age groups (children, adults, or the elderly) (14)(15)(16) or special occupation groups (health care workers or military personnel) (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%